Efficient Vertical-Cavity Mid-IR Thermal Radiation to Silicon-Slab Waveguide Coupling Using a Shallow Blazed Grating - Gerald Pühringer; Bernhard Jakoby (Proceedings, 2017)
In this work we investigate the coupling of radiation originating from a vertical-cavity enhanced thermal emitter (VERTE) into an optical waveguide, which can, for instance, act as a sensing element. We present full wave modelling results demonstrating highly efficient emitter-to-waveguide diffraction coupling at multiple angles using the previously designed VERTE together with a shallow blazed grating. It is shown that the coherent and dispersive thermal emission of the VERTE concept is well suited to achieve highly efficient and integrated mode coupling in the mid IR region.